2023
DOI: 10.3390/app13179680
|View full text |Cite
|
Sign up to set email alerts
|

Closely-Spaced Repetitions of CAMTA Trans-Factor Binding Sites in Promoters of Model Plant MEP Pathway Genes

Piotr Szymczyk

Abstract: Previous research has demonstrated the presence of two closely spaced repetitions of the rapid stress-responsive cis-active element RSRE (G/A/C)CGCG(C/G/T) in the 5′UTR of S. miltiorrhiza2C-methyl-D-erithrytol 2,4-cyclodiphosphate synthase (MECPS) gene. The product of MECPS activity, represented by 2C-methyl-D-erithrytol 2,4-cyclodiphosphate (MECPD), indicates its retrograde regulatory role and activates CAMTA trans-factors. Since the complete activation of CAMTA trans-factors requires the cooperative interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…7,8,24 In the model plant which is induced GGPS gene as a structural enzyme in the terpenoid biosynthesis pathway. 12,13,14,25 In this study, the expression of two of the seven teak GGPS, namely the GGPS3 and GGPS6 genes have an expression pattern of up and down-regulation as part of the terpenoid biosynthesis process in young and old leaves. The results of DEG and qRT PCR gene expression analysis showed that GGPS6 maintained the up-regulation trend in the regulation of terpenoid formation.…”
Section: The Ggps3 and Ggps6 Expression Profiles In Teak Leavesmentioning
confidence: 88%
See 1 more Smart Citation
“…7,8,24 In the model plant which is induced GGPS gene as a structural enzyme in the terpenoid biosynthesis pathway. 12,13,14,25 In this study, the expression of two of the seven teak GGPS, namely the GGPS3 and GGPS6 genes have an expression pattern of up and down-regulation as part of the terpenoid biosynthesis process in young and old leaves. The results of DEG and qRT PCR gene expression analysis showed that GGPS6 maintained the up-regulation trend in the regulation of terpenoid formation.…”
Section: The Ggps3 and Ggps6 Expression Profiles In Teak Leavesmentioning
confidence: 88%
“…Geranylgeranyl pyrophosphate synthase (GGPS) is a structural enzyme in the terpene biosynthesis pathway and a member of the isopentenyl pyrophosphate synthase gene family. 11,13 In recent years, some progress has been made in the functional research of GGPS genes. The physiological and biochemical functions of GGPS are closely related to its tissue expression characteristics and subcellular localization.…”
Section: Introductionmentioning
confidence: 99%